Random antimicrobial peptide mixtures as non-antibiotic antimicrobial agents for cultured meat industry - Idan Yakir; Einav Cohen; Sharon Schlesinger; Zvi Hayouka (Food Chemistry: Molecular Sciences)
Antibiotics, commonly used in cell culture studies to prevent microbial contamination, cannot be employed in Cultured meat (CM) due to potential residues in the final food products. Hence, there is an urgent need to develop novel and safe non-antibiotic antimicrobial agents. Here, we investigated the potential of random antimicrobial peptide mixtures (RPMs) as non-antibiotic antimicrobial agents. RPMs are synthetic peptide cocktails that have previously shown strong and broad antimicrobial activity; however, their use in cell culture media and their effect on mammalian cells have not yet been explored. Here we show that RPMs had no significant impact on mesenchymal stem cells (MSCs) at concentrations that effectively inhibit bacterial growth. RPMs displayed strong bactericidal activity against Gram-positive bacteria, achieving a 6-log reduction of L. monocytogenes in cell culture medium without any cytotoxicity. Additionally, RPMs showed a low occurrence of resistance development with no significant resistance developed in compared with a combination of penicillin and streptomycin. Moreover, LK20 mixture was rapidly digested and a rapid digestion in a simulated digestion model. Our results indicate that RPMs have great potential to serve as safe and effective non antibiotic antimicrobial agents in cultured meat industry.